Prospects for the use of the fibrinolytic drug streptokinase - Arseniuk, A.S.; Poshtarenko, A.V.; Reshetnyak, L.R. (Problems of Environmental Biotechnology, 2023)
The report considers the prospects of using the fibrinolytic drug streptokinase in the treatment of cardiovascular diseases. Special attention is paid to streptokinase as an effective means for the treatment of myocardial infarction, especially in economically weak countries. The advantages of using streptokinase in terms of efficiency and economic feasibility compared to other clot dissolvers are highlighted. The need for further research and optimization of the production technology of fibrinolytic enzymes to overcome the limitations associated with their use is explained.